What do you do when you have to program for an athlete with an injury? - Bennett, S. (Strength and Conditioning Journal, 2009)
The strength and conditioning coach often is faced with designing a conditioning program for an injured athlete in different phases of the rehabilitation/return to play process. As a strength and conditioning coach, what do you do when you have to program for an athlete with injury?